Group Counseling Services with a Reality Approach in Alleviating Learning Difficulties for Students at Mts NW Senyiur - Marfuatun Marfuatun; Ermi Yuliana; Dewi Yulianti (Educatio, 2022)
Group counseling services with a realistic approach to alleviating students' learning difficulties at Mts NW Senyiur. This study aims to determine reality group counseling services in helping learning difficulties for students at VIII MTs NW Senyiur. The type of this research is a Pre-Experimental design with One-Group Pretest-Posttest Design. The population of this study was all students of class VIII MTs NW Senyiur totaling 25 students. Data collection techniques using questionnaires and observations, analysis using quantitative data in numbers processed using simple statistics. This study indicates that the initial condition data before being given treatment (pretest) in the form of group counseling services are in the low category with a score of 24.4. After being provided treatment (posttest) group counseling services, the condition is in the high sort with a score of 80, the average score of the scale learning difficulties in the experimental class with the highest score of 17,325. Thus, reality group counseling services affect alleviate learning difficulties for class VIII MTs NW Senyiur students.